The association of body mass index and its interaction with family history of dyslipidemia towards dyslipidemia in patients with type 2 diabetes: a cross-sectional study in Zhejiang Province, China - Chen, Xiang-Yu; Fang, Le; Zhang, Jie; Zhong, Jie-Ming; Lin, Jing-Jing; Lu, Feng (Frontiers in Public Health, 2023)
Objectives: This study aimed to investigate the association between body mass index (BMI) and dyslipidemia and to explore the interaction between BMI and family history of dyslipidemia towards dyslipidemia in patients with type 2 diabetes. Methods: This cross-sectional study was conducted between March and November 2018 in Zhejiang Province, China. A total of 1,756 patients with type 2 diabetes were included, physical examination data, fasting blood samples and face-to-face questionnaire survey data were collected. Restricted cubic spline analysis was used to evaluate the association between BMI and the risk of dyslipidemia. Unconditional multivariable logistic regression was used to estimate the interaction between BMI and family history of dyslipidemia towards dyslipidemia. Results: The prevalence of dyslipidemia was 53.7% in the study population. The risk of dyslipidemia elevated with increased BMI value (p for non-linearity<0.05). After adjusting for covariates, individuals with high BMI (≥24 kg/m²) and a family history of dyslipidemia had a 4.50-fold (95% CI: 2.99-6.78) increased risk of dyslipidemia compared to the normal reference group, which was higher than the risk associated with high BMI alone (OR=1.83, 95% CI: 1.47-2.28) or family history of dyslipidemia alone (OR=1.79 95% CI: 1.14-2.83). Significant additive interaction between high BMI and a family history of dyslipidemia was detected, with RERI, AP, and SI values of 1.88 (95% CI: 0.17-4.10), 0.42 (95% CI: 0.02-0.62), and 2.16 (95% CI: 1.07-4.37), respectively. However, stratified by status of diabetes control, this additive interaction was only find significant among patients with controlled diabetes. Conclusions: Both high BMI and a family history of dyslipidemia were related with high risk of dyslipidemia. Moreover, there were synergistic interaction between these two factors. Patients with type 2 diabetes who had a family history of dyslipidemia were more susceptible to the negative impact of being overweight or obesity on dyslipidemia.